DAKWAH STRATEGIES IN INCREASING THE SPIRIT OF LOVE FOR THE QURANTO STUDENTS OF ASSUDANIYAH ISLAMIC BOARDING SCHOOL IN MEDAN (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2026)
Cottage Islamic boarding school as institution Islamic education has role important in form character and spirituality students through integration the values of the Qur'an. However, in the digital era, motivation intrinsic students For love the Qur'an often hampered by dominance motivation extrinsic and gadget influences , so that requires an effective da'wah strategy especially in Pondok Islamic boarding school Assudaniyah Medan. Research This aim For knowing the strategy of preaching For increase Spirit love the Qur'an, analyzing factor supporters and inhibitors , as well as formulate recommendation strategic . Research This use approach qualitative with design studies cases that are carried out through observation participants , semi- structured interviews , and analysis documentation to subject like figures , ustadz , musyrif , and santri . Data analysis was carried out with using the interactive model of Miles and Huberman, to ensure validity through triangulation . Research results revealing the strategy of preaching comprehensive which includes motivation sustainable , method learning diverse , and approaches emotional -spiritual. The strategy proven effective in build motivation intrinsic , accompanied by recommendation approach contextual-humanist for manager Islamic boarding school in face dynamics modernization .